Irreversibility and Aggregate Investment - Bertola, G.; Caballero, R. J. (Review of Economic Studies, 1994)
Investment is often irreversible: once installed, capital has little or no value unless used in production. This paper proposes and solves a model of sequential irreversible investment and characterizes the aggregate implications of microeconomic irreversibility and idiosyncratic uncertainty. If a large amount of idiosyncratic uncertainty is allowed for, the distributional dynamics induced by the nonlinear character of irreversible investment policies are capable of smoothing the dynamics of aggregate investment (relative to those of its forcing processes) to the extent required by U.S. data.